Two new plays Unexpected tenderness and Fighting over Beverley - Horovitz, Israel (Garden City, N.Y. Fireside Theatre, 1994)
Unexpected Tenderness is a poignant drama about a dysfunctional Jewish family in Massachusetts, structured as a memory play. Roddy Stern recalls what it was like growing up in a family dominated by his paranoid father, a truck driver who lurked outside his house instead of working to catch his wife with other men. A long suffering and abused saint, Roddy's mother raised two children in this difficult environment. Roddy's complex father is portrayed as a loving man with a demon inside that he fights but cannot exorcize. He eventually loses all control and drives away the family he loves.
Fighting Over Beverley is a romantic comedy that portrays a love triangle among three septuagenarians. The focal point is Beverley Shimma wooed by both the British fiance she dumped at the end of World War II (Archie Bennett) and the dashing American husband she left him for (Zelly Shimma).
Unexpected tenderness -- Fighting over Beverley.